Comparative Numerical Study of Sleeve Fuse Systems and RBS for Enhancing Cyclic Performance in Steel End-Plate Connections - Atar, Muhammed (Korean Soc Steel Construction-Kssc, 2025)
This study introduces a sleeve fuse system to improve the cyclic performance of steel end-plate connections. A specially designed steel sleeve, placed between the end plate and nut/washer, disrupts the load path and enhances ductility. Experimental models from the literature were used for model validation, ensuring high accuracy in the numerical analysis. Simulations of various sleeve geometries, using a validated finite element model, demonstrate the system's effectiveness. A comparative analysis with reduced beam sections (RBS) and standard connections highlights the superior performance of the sleeve system, a key novelty of this study. A hybrid design combining the sleeve system with RBS is also proposed. Results show that the sleeve system improves rotational capacity, acting as a structural fuse during seismic events by enhancing ductility and energy absorption. Increased bolt elongation further boosts rotational capacity, enhancing frame robustness. The proposed system offers a superior alternative to conventional methods with improved ductility and energy dissipation.
Keywords: Steel structures; Fuse system; RBS connection; Energy dissipation; Rotational capacity; Retrofitting